2021
DOI: 10.3390/electronics10202465
|View full text |Cite
|
Sign up to set email alerts
|

The Decision-Making Process and the Construction of Online Sociality through the Digital Storytelling Methodology

Abstract: Digital storytelling (DST) is a teaching methodology (and tool) that is very widespread in different types of training: formal and informal, professional, and for adults. Presently, education is evolving and moving towards digital storytelling, starting from the models of Lambert and Olher. Today, although DST is usually used in the training that students receive for narrative learning, experimentation on the psychological and social consequences of this online teaching practice is still scarce. The literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The intervention, called 'DST music and soundtracks', was constituted in the model of the University of Foggia (present below) (Limone et al, 2021) in a theoretical lesson on listening to music, musical intelligence and three international good practices (Toto, 2017) of technology-mediated music teaching in which students observe student treatment, behaviour and outcomes of this teaching practice. As an alternative to the latter theme, it is possible to replace it with a lesson on rhythm for which no prior knowledge of musical content is required.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention, called 'DST music and soundtracks', was constituted in the model of the University of Foggia (present below) (Limone et al, 2021) in a theoretical lesson on listening to music, musical intelligence and three international good practices (Toto, 2017) of technology-mediated music teaching in which students observe student treatment, behaviour and outcomes of this teaching practice. As an alternative to the latter theme, it is possible to replace it with a lesson on rhythm for which no prior knowledge of musical content is required.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention, called 'DST music and soundtracks', was constituted in the model of the University of Foggia (present below) (Limone et al, 2021) in a theoretical lesson on listening to music, musical intelligence and three international good practices (Toto, 2017) of technology-mediated music teaching in which students observe student treatment, behaviour and outcomes of this teaching practice. As an alternative to the latter theme, it is possible to replace it with a lesson on rhythm for which no prior knowledge of musical content is required.…”
Section: Methodsmentioning
confidence: 99%
“…Undoubtedly, the new audiovisual theory was suggested mostly for adult media studies learners and targeted at the educational process quality utilizing technology-enhanced learning [4]. Additionally, on the other hand, following the relevant literature [51,116,120,[186][187][188][189][190], the digital storytelling methodology focuses on the application of digital storytelling (narration form here on) through educational techniques which is commonly created and used from and through ICT-tools in order to bring a narrative to life utilizing audiovisual content [4,8,177]. Despite what we already know about the influence of the ICTs in education and ICT-supported educational techniques [4] (p. 8), the most recent literature has also shown that their effectiveness is determined by the educational needs of the learners themselves [1,4,8].…”
Section: Research Interactive Seminar: the Teaching Methodological Ap...mentioning
confidence: 99%